Polyphenol-Rich Beverages and Mental Health Outcomes - Agnieszka Micek; Joanna Jurek; Marcin Owczarek; Ida Guerrera; Sebastiano Alfio Torrisi; Sabrina Castellano; Giuseppe Grosso; Ali A. Alshatwi; Justyna Godos (MDPI AG, 2023)
Emerging evidence suggests that diets rich in plant-based foods and beverages may exert plausible effects on human health tackling the risk of chronic diseases. Although the data are promising for numerous outcomes, including cardiovascular diseases, the data on mental health are limited. The aim of this study was to investigate the association between individual polyphenol-rich beverages intake and mental health outcomes, such as perceived stress, depressive symptoms, and sleep quality, among adult individuals living in the Mediterranean area. The demographic and dietary characteristics of a sample of 1572 adults living in southern Italy were analysed. Multivariate logistic regression analyses, controlling for confounding factors, were used to calculate odds ratios (ORs) and 95% confidence intervals (CIs) of the association between individual polyphenol-rich and alcoholic beverages containing polyphenols and mental health outcomes. The multivariate model adjusted for background covariates and the Mediterranean diet showed that individuals with a moderate intake (up to 1 cup/glass per day) of coffee and tea were less likely to have high perceived stress (OR = 0.61, 95% CI: 0.45-0.84) and depressive symptoms (OR = 0.56, 95% CI: 0.39-0.80), respectively. Furthermore, regular coffee and moderate/regular red wine drinkers were less likely to have depressive symptoms (OR = 0.72, 95% CI: 0.54-0.95 and OR = 0.74, 95% CI: 0.54-0.99, respectively). No significant associations were retrieved for the intake of polyphenol-rich and alcoholic beverages and sleep quality. In conclusion, the results of the present study suggest that polyphenol-rich beverages may be associated with mental health, in terms of depressive symptoms and perceived stress. Nonetheless, further research exploring how the polyphenol-rich beverages impact brain health and what the optimal patterns of consumption are for different populations are warranted.